Degradación que sufre la calidad del camarón por efectos de la manipulación, en el Mercado 25 de junio de la ciudad de Machala - Quevedo Gálvez, Sandra E. (2013)
The present research was conducted in the city of Machala, whose theme was ¨suffering degradation shrimp quality by effects of manipulation in the market on June 15 in the city of Machala¨. This research deals with the organoleptic (color, smell, texture, pH measurement) and bacteriological fresh shrimp as well as health conditions that are recorded level outlets to prevent further contamination.